#### Question

Using the Remainder Theorem, factorise each of the following completely

x^{3} + x^{2} – 4x – 4

#### Solution

`f(x)=x^3+x^2-4x-4`

`for x=1,`

`f(x)=f(-1)=(-1)^3+(-1)^2-4(-1)-4`

`=-1+1+4-4=0`

`"Hence, (x+1) is a factor of f (x)" `

∴ `x^3+x^2-4x-4=(x+1)(x^2-4)`

`= (x+1) (x+2) (x-2) `

Is there an error in this question or solution?

Advertisement

Advertisement

Solution Using the Remainder Theorem, Factorise Each of the Following Completely X3 + X2 – 4x – 4 Concept: Factorising a Polynomial Completely After Obtaining One Factor by Factor Theorem.

Advertisement